2022
DOI: 10.1177/10760296221093595
|View full text |Cite
|
Sign up to set email alerts
|

The Extensive Regulation of MicroRNA in Immune Thrombocytopenia

Abstract: MicroRNA (miRNA) is a small, single-stranded, non-coding RNA molecule that plays a variety of key roles in different biological processes through post-transcriptional regulation of gene expression. MiRNA has been proved to be a variety of cellular processes involved in development, differentiation, signal transduction, and is an important regulator of immune and autoimmune diseases. Therefore, it may act as potent modulators of the immune system and play an important role in the development of several autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 192 publications
0
7
0
Order By: Relevance
“…Thus, it can act as a modulator of the immune system and can play an important role in the development of several autoimmune diseases [ 15 ]. Several studies have suggested that miRNAs are involved in the pathogenesis of ITP, because they can interact with the function of adaptive and innate immune responses [ 16 ]. The relationship between the mechanism of action of miRNA and ITP is complex and still only partially known.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can act as a modulator of the immune system and can play an important role in the development of several autoimmune diseases [ 15 ]. Several studies have suggested that miRNAs are involved in the pathogenesis of ITP, because they can interact with the function of adaptive and innate immune responses [ 16 ]. The relationship between the mechanism of action of miRNA and ITP is complex and still only partially known.…”
Section: Discussionmentioning
confidence: 99%
“…miR-4482 has been previously reported to have differential expression in several diseases such as pediatric embryonal central nervous system neoplasms [ 34 ], immune thrombocytopenia [ 35 , 36 ], and infections [ 37 ]. Similarly, miR-3912 is differentially expressed in papillary thyroid cancer patients [ 38 ] and pediatric embryonal central nervous system neoplasms [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Veiga et al found that miR-155 is a key positive regulator of regulatory T cells (Tregs) [22] . At the same time, studies have shown that miRNAs play an important role in hematopoietic differentiation, which is related to the cellular immune response leading to ITP [23] . Zuo et al found that miR-4739 significantly increased in ITP [24] .…”
Section: And Figmentioning
confidence: 99%